Validation Method for Simultaneous Analysis of Betamethasone Dipropionate and Retinoic Acid in Cream Formulation by Ultra High-Performance Liquid Chromatography - Supandi, Supandi; Mansyur, Umar; Ranie, Annisa Ananda; Ulya, Linda Mazroatul (UI Scholars Hub, 2021)
A simple, precise and rapid reverse phase UHPLC-PDA method has been developed and validated for the simultaneous analysis of betamethasone dipropionate (BTM) and retinoic acid (REA) in whitening cream dosage form. The mixture of betamethasone dipropionate (BTM) and retinoic acid (REA) was separated on Phenomenex Bonclone 10 C18 (150 mm x 3.9 mm) column. All separations were performed with a Dionex 3000 Photodiode Array (PDA) detector on 240 nm and 340 nm wavelength, column temperature at 40oC, and flow rate at 1.0 ml/min. The mobile phase was methanol-acetic acid 0.1% (85:15) with pH 5. The retention times of BTM and REA were found to be 1.90 and 3.70 minutes, respectively. The method showed good linearity with correlation coefficients of 0.9998 and 1.0000 over the ranges of 5-25 ppm for BTM and 25-200 ppm for REA, respectively. The method has mean recoveries in the range of 99.37% to 100.94% for all analytes. The developed method can be used in the routine analysis of BTM and REA in cream formulation, as well as for qualitative analysis in whitening cosmetic preparations or for quantitative analysis in drug preparations.